Practical Recommendations for the Diagnosis and Medical Management of Stable Angina: An Expert Panel Consensus. Issue 4 (October 2019) - Farmakis, Dimitrios; Andrikopoulos, George; Giamouzis, Gregory; Giannakoulas, George; Poulimenos, Leonidas; Skalidis, Emmanouil; Vlachopoulos, Charalambos; Parissis, John
Abstract : Abstract: Stable angina affects a significant number of coronary artery disease patients, impairing their quality of life and worsening their prognosis. It manifests even despite a history of revascularization and is often poorly controlled with drug therapy. Comorbid conditions are frequently encountered in coronary artery disease patients, affecting their prognosis and rendering the diagnosis and management of angina more challenging. In this article, derived by an expert panel meeting, we attempt a practical approach to stable angina, focusing on symptomatic patients subjected to previous coronary revascularization or not suitable for revascularization and providing handy diagnostic and therapeutic algorithms and comorbidity-adjusted therapeutic approaches in accordance with existing evidence, current recommendations, and locally available therapeutic options.